2012
DOI: 10.1139/v2012-073
|View full text |Cite
|
Sign up to set email alerts
|

Unnatural C-1 homologues of pancratistatin — Synthesis and promising biological activities

Abstract: Several C-1 homologues of pancratistatin and 7-deoxypancratistatin were synthesized by a phenanthrene–phenathridone oxidative recyclization strategy. The key steps involved the enzymatic dihydroxylation of bromobenzene, addition of an aryl alane to an epoxyaziridine, an intramolecular aziridine opening on silica gel in solid phase, and the above-mentioned recylization strategy. Experimental and spectral data are reported for all new compounds. All synthesized C-1 homologues of pancratistatin and 7-deoxypancrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 43 publications
(35 reference statements)
0
20
0
3
Order By: Relevance
“…In our previous study it has been shown 2r,t that C-1 analogues 20 and 21 also displayed pronounced activity against pancreatic (BxPC-3), prostate (DU-145), and lung (NCI-H460) cancer cell lines. The respective IC 50 values for these three lines for C-1 acetate 20 were 0.07, 0.06 and 0.07 μM and for C-1 benzoate 21 : 0.01, 0.01.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…In our previous study it has been shown 2r,t that C-1 analogues 20 and 21 also displayed pronounced activity against pancreatic (BxPC-3), prostate (DU-145), and lung (NCI-H460) cancer cell lines. The respective IC 50 values for these three lines for C-1 acetate 20 were 0.07, 0.06 and 0.07 μM and for C-1 benzoate 21 : 0.01, 0.01.…”
mentioning
confidence: 96%
“…1 Many unnatural or truncated derivatives of pancratistatin have been prepared and evaluated for biological activity with the intent to produce more bioavailable agents then the highly water-insoluble natural products. 2 …”
mentioning
confidence: 99%
See 3 more Smart Citations